Effect Self Help Group On Coping Mechanism Focused Problem Coping In Adolescents SMK Negeri Kediri - Purnomo Purnomo; Suciati Suciati (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
Coping mechanism is a method used by someone to reduce the stress level experienced by an individual. One of the problems experienced by adolescents is stress. The impact of stress cause’s problems on physical health and reduce psychological abilities adolescents. One of the supports in improving coping mechanism Problem Focused Coping (PFC) on adolescents used intervention Self Help Group. Purpose in thus study to determine the effect Self Help Group to improved Coping Mechanisms: Problem Focused Coping (PFC) on adolescents. Design in this study by Quasi Experimental Pre-Test and Post-Test With Control Group. Samples in this study with the control and exclusion criteria with the number of respondents 282 students, which were divided into 141 in the control group and the intervention group. Collecting data used the Problem Focused Coping questionnaire from A-COPE. Analysis by used SPSS 16.0 for windows with Corelation Pearson Product Moments Test. Results in this study indicate the coping mechanism problem focused coping control group obtained p value=0.293, and the intervention group p=0.000. The results this study prove the Self-Help Group intervention has an influence increasing positive coping mechanisms towards Problem Focused Coping (PFC). Conclusion Self Help group intervention has a significant effect in increasing the coping mechanism of problem focused coping (PFC) in adolescents.